Is the Whole Greater than the Sum of its Parts? : Strengthening Caribbean Regional Integration - Al-Hassan, Abdullah (IMF Working Papers; Working Paper ;, 2020)
Deeper economic integration within the Caribbean has been a regional policy priority since the establishment of the Caribbean Community (CARICOM) and the decision to create the Caribbean Single Market and Economy (CSME). Implementation of integration initiatives has, however, been slow, despite the stated commitment of political leaders. The 'implementation deficit' has led to skepticism about completing the CSME and controversy regarding its benefits. This paper analyzes how Caribbean integration has evolved, discusses the obstacles to progress, and explores the potential benefits from greater integration. It argues that further economic integration through liberalization of trade and labor mobility can generate significant macroeconomic benefits, but slow progress in completing the institutional arrangements has hindered implementation of the essential components of the CSME and progress in economic integration. Advancing institutional integration through harmonization and rationalization of key institutions and processes can reduce the fixed costs of institutions, providing the needed scale and boost to regional integration. Greater cooperation in several functional policy areas where the region is facing common challenges can also provide low-hanging fruit, creating momentum toward full integration as the Community continues to address the obstacles to full economic integration.